Glucocorticoid receptors signaling impairment potentiates amyloid‐β oligomers‐induced pathology in an acute model of Alzheimer's disease. Issue 1 (29th November 2019) - Canet, Geoffrey; Pineau, Fanny; Zussy, Charleine; Hernandez, Célia; Hunt, Hazel; Chevallier, Nathalie; Perrier, Véronique; Torrent, Joan; Belanoff, Joseph K.; Meijer, Onno C.; Desrumaux, Catherine; Givalois, Laurent
Abstract: Dysregulation of the hypothalamic‐pituitary‐adrenal (HPA) axis occurs early in Alzheimer's disease (AD), associated with elevated circulating glucocorticoids (GC) and glucocorticoid receptors (GR) signaling impairment. However, the precise role of GR in the pathophysiology of AD remains unclear. Using an acute model of AD induced by the intracerebroventricular injection of amyloid‐β oligomers (oAβ), we analyzed cellular and behavioral hallmarks of AD, GR signaling pathways, processing of amyloid precursor protein, and enzymes involved in Tau phosphorylation. We focused on the prefrontal cortex (PFC), particularly rich in GR, early altered in AD and involved in HPA axis control and cognitive functions. We found that oAβ impaired cognitive and emotional behaviors, increased plasma GC levels, synaptic deficits, apoptosis and neuroinflammatory processes. Moreover, oAβ potentiated the amyloidogenic pathway and enzymes involved both in Tau hyperphosphorylation and GR activation. Treatment with a selective GR modulator (sGRm) normalized plasma GC levels and all behavioral and biochemical parameters analyzed. GR seems to occupy a central position in the pathophysiology of AD. Deregulation of the HPA axis and a feed‐forward effect on PFC GR sensitivity could participate in the etiology of AD, in perturbing Aβ and Tau homeostasis. These results also reinforce the therapeutic potential of sGRm in AD.